Luteolin induces pyroptosis in HT-29 cells by activating the Caspase1/Gasdermin D signalling pathway - Chen, Yiliu; Ma, Shengsuo; Pi, Dajin; Wu, Yingchao; Zuo, Qian; Li, Chongan; Ouyang, Mingzi (Frontiers in Pharmacology, 2022)
As a natural flavonoid, luteolin contains anti-inflammatory, antioxidant, and anticancer properties. Luteolin has been proven in numerous studies to limit the growth of a range of cancer cells by triggering apoptosis, autophagy, and cell cycle arrest in tumor cells. However, in vivo research has been restricted. In addition, other studies have shown that luteolin has a good inhibitory effect on apoptosis resistant cancer cells. While the mechanism of the existing research is not perfect to explain this phenomenon, we assume that luteolin, as a type of natural compound that is effective through various channels, may have potential mechanisms to inhibit tumor growth. In our study, we proved that luteolin had a good inhibitory effect on the proliferation of colon cancer by CCK8 and EDU fluorescence staining experiments, and the same conclusion was also reached in animal experiments. In addition, we found that luteolin, an antioxidant, unexpectedly promotes oxidative stress by measuring oxidative balance related indicators such as ROS, SOD, H2O2 and GSH. However, reduction of the oxidation level of luteolin treated HT-29 cells with active oxygen scavengers NAC did not restore cell growth inhibition. However, the Caspase1 inhibitor VX765 reversed cell growth inhibition. Western Blot analysis showed that luteolin treatment increased the expression of Caspase1, GasderminD and IL-1β in the pyroptosis signaling pathways of colon cancer. We further intuitively observed NLRP3/GasderminD co-expression in luteolin treated HT-29 cells and mouse tumor tissues by immunofluorescence co-localization. These results suggest that luteolin inhibits the proliferation of colon cancer through a novel pathway called pyroptosis. It provides a new idea for the development of natural products to inhibit tumor growth by inducing pyroptosis.